Production of soap from sesamum indicum (sesame seed) - Veroneka, Semilin (2014)
Sesame (Sesamum indicum L.) seed is the oldest oil seed crop and the highest content of fats and oils among other seeds oil. The fats and oils of sesame contain good proteins and vitamins for body health and food. This research presents the study of soap from undehulled (coated) and dehulled sesame seed oil which derived from a soxhlet extraction method. Different treats of sesame seed were exposed to experiment that determine the value of physiochemical, such as saponification value (SV), acid value (AV), iodine value (IV), free fatty acid value (FFA) and peroxide value (PV). Sesame oils were saponified with two types of alkali which sodium hydroxide (NaOH) and potassium hydroxide (KOH) to give a solid and liquid soap, respectively. The analysis of the soap was carried out to determine the pH value, foam height, colour in solution, and solubility in water and foam structure. Further analysis of the soap was testing with a dirty cloth, hand washing and laboratory glassware. Results from the analysis were exposed that sesame seed can produce either solid or liquid soap with high of conditioning agent. Dehulled oil has saponification value of 186.5 mg KOH/ g, acid value of 109.4 g I2/100g, peroxide value of 14.8 meq H2O2/g, and free fatty acid value of 49.3 % (oleic) and undehulled seed oil has values 210.4 mg KOH/ g, 1.34 g I2/100g, 106.3 meq H2O2/g, 8 and 39.48 % (Oleic), respectively. In conclusion, the objective of this study is achieved where sesame seed soap can be established, whether from undehulled or dehulled oil. In future, sesame oil is potentially to use as an oil foundation in making soap